Semen Quality of KUB Chicken in Ringer Lactate-Egg Yolk Diluent with Carrot Extract Supplementation During Cold Storage - Udrayana, Setya Budhi; Iswati, Iswati; Bintari, Intan Galuh; Bakar, Abu (Buletin Peternakan, 2025)
This study aimed to determine the quality of chicken semen from Kampung Unggulan Balitbangtan (KUB) in Ringer lactate-egg yolk diluent with carrot extract supplementation during cold storage. A total of 6 KUB males were selected for the experiment and each of them was subjected to 5 collections of semen. The experiment was performed using a Randomized Block Design (RBD) with 4 treatments. These treatments included P0 (100% Ringer lacate-egg yolk without carrot extract), P1 (80% Ringer lacate-egg yolk + 20% carrot extract), P2 (60% Ringer lacate-egg yolk + 40% carrot extract), P3 (Ringer lactate yolk 40% + 60% carrot extract). The research variables consisted of motility, viability, abnormalities of spermatozoa, and plasma membrane integrity. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's test. It was discovered that the percentage of motility and viability up to 48 hours of storage showed significant differences (p<0.05) between treatments. The best results were in group P2, with motility and viability being 40.33 ± 6.60% and 60.86 ± 7.84%, respectively. Abnormalities of spermatozoa up to 24 hours of storage showed significant differences (p<0.05) between treatments, and not significantly different (p>0.05) at 48 hours of storage. Furthermore, plasma membrane integrity failed to show a significant difference between groups at 1 hour of storage and was significantly different (p<0.05) at 24 and 48 hours of storage. The best or the highest result is in the P2 group, with plasma membrane integrity being 71.89 ± 2.40%. It was concluded that the use of 40% carrot extract supplementation in Ringer lacate-egg yolk diluent tends to maintain the quality of KUB chicken semen in cold storage for up to 48 hours and was suitable for the application of artificial insemination.